Examining the Maqāṣid Al-Qur’an: Understanding ‘Abdul Karīm Hāmidī’s Approach to Tafsir for Achieving Human Welfare: Menelaah Maqāṣid Al-Qur’an: Memahami Pendekatan Tafsir ‘Abdul Karīm Hāmidī untuk Mencapai Kemaslahatan Manusia - Sahlan, Azis; Siti Khotijah (Aqwal: Journal of Qur'an and Hadis Studies, 2024)
Background and Objetives: This research focus on Maqāṣidi tafsir on Abdul Karim Hāmidī's Maqāṣid Al-Qur'ān perspective’s, with the aim of describing the construction of his thoughts. This research is based on the importance of understanding the main purpose of the revelation of the Qur'an in order to achieve the benefit of mankind, as well as the Maqāṣid Al-Qur'an in Hāmidī's perspective. Methodology: library research, which involves analyzing primary and secondary literature related to Maqāṣid Al-Qur'an and Maqāṣidi tafsir. Main findings: Hāmidī defines Maqāṣid Qur'ān as the main purpose for which the Qur'ān was revealed to realize the benefit of the servants. Hāmidī's division of Qur'ānic Maqāṣid includes three main parts: Maqāṣid ammah (general), Maqāṣid khassah (specific), and Maqāṣid juz'iyah (part). In addition, it was found that Qur'ānic Maqāṣid has a broader scope than sharia Maqāṣid. Contributions: a more systematic understanding of the division of the Qur'ānic Maqāṣid based on Hāmidī's thought, as well as enriching Maqāṣidi tafsir methodology by elaborating various ideas from previous figures. This research also raises awareness of the importance of understanding the Maqāṣid and wisdom of the Qur'anic verses to achieve the benefit of humanity, both in this world and in the hereafter. Conclusion: an in-depth understanding of the Maqāṣid of the Qur'an can reveal the beauty and virtue of the Qur'an and avoid the error of takwil. Although this study has limitations such as limited literary sources and a limited focus on Hāmidī's thought, the results make a significant contribution to the development of Maqāṣid Qur'ān studies and Maqāṣidi tafsir methodology.